Criterion-Related Validity of Spectroscopy-Based Skin Carotenoid Measurements as a Proxy for Fruit and Vegetable Intake: A Systematic Review - Radtke, Marcela D (Adv Nutr, 2020)
Carotenoids are a category of health-promoting phytonutrients that are found in a variety of fruits and vegetables and have been used as a biomarker to approximate dietary fruit and vegetable (F/V) intake. Carotenoids are consumed, metabolized, and deposited in blood, skin, and other tissues. Emerging evidence suggests spectroscopy-based skin carotenoid measurement is a noninvasive method to approximate F/V intake. Spectroscopy-based skin carotenoid measurement overcomes bias and error inherent in self-reported dietary recall methods, and the challenges in obtaining, storing, and processing invasive blood samples. The objective of this systematic review was to examine criterion-related validity of spectroscopy-based skin carotenoid measurement as a proxy for F/V intake. The 3 methods examined were resonance Raman spectroscopy (RRS), pressure-mediated reflection spectroscopy (RS), and spectrophotometers. A comprehensive literature search of PubMed, Excerpta Medica Database (Embase), Cumulative Index of Nursing and Allied Health Literature (CINAHL), ProQuest, Cochrane Database of Systematic Reviews, and Cochrane Central Register of Controlled Trials (CENTRAL) was performed in December 2018, yielding 7931 citations. Studies that examined associations between spectroscopy, blood carotenoids, and/or dietary intake were identified and reviewed independently by ≥2 reviewers to determine eligibility for inclusion. Twenty-nine articles met the inclusion criteria and all 29 studies found significant correlations or associations between spectroscopy-based skin carotenoids and plasma or serum carotenoids and/or dietary F/V intake. A majority of the studies evaluated carotenoid concentration in adults; however, 4 studies were conducted in infants and 6 studies evaluated children. Twenty studies specified the racial/ethnic groups from which the samples were drawn, with 6 including ≥20% of the sample from a minority, nonwhite population. The findings of this systematic review support the use of spectroscopy for estimating F/V intake in diverse human populations, although additional validation is needed, particularly among racially/ethnically diverse populations and populations of varying ages.